1994
DOI: 10.1111/j.1432-1033.1994.tb20085.x
|View full text |Cite
|
Sign up to set email alerts
|

Ca2+ Binding to Cardiac Troponin C in the Myofilament Lattice and Its Relation to the Myofibrillar ATPase Activity

Abstract: The Ca2+‐binding properties of troponin C in the intact myofilament lattice and their relation to the activation of ATPase were investigated with isolated porcine cardiac myofibrils. Ca2+ binding, which is composed of two classes of binding sites with different affinities (classes 1 and 2), was clearly detected by a novel method for subtracting the large background activity of myofibrillar Ca2+ binding. The classes 1 and 2 were equivalent stoichiometrically to the two high‐affinity sites (sites III and IV) and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
17
0

Year Published

2000
2000
2012
2012

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(17 citation statements)
references
References 39 publications
0
17
0
Order By: Relevance
“…This raises the possibility that the increased buffering is a property of the endogenous Ca 21 buffer(s). Since most EF-hand Ca 21 binding proteins have four Ca 21 binding sites and cooperativity has been observed in several cases, including troponin-C (Iida, 1988;Morimoto and Ohtsuki, 1994;Teleman et al, 1983), calmodulin (Olwin and Storm, 1985), and calbindin (Leathers et al, 1990), we thought that positive cooperativity might achieve the observed result. For the simulations shown in Fig.…”
Section: A Virtual Cell To Explain Dynamic Ca 21 Redistributions Durimentioning
confidence: 90%
See 1 more Smart Citation
“…This raises the possibility that the increased buffering is a property of the endogenous Ca 21 buffer(s). Since most EF-hand Ca 21 binding proteins have four Ca 21 binding sites and cooperativity has been observed in several cases, including troponin-C (Iida, 1988;Morimoto and Ohtsuki, 1994;Teleman et al, 1983), calmodulin (Olwin and Storm, 1985), and calbindin (Leathers et al, 1990), we thought that positive cooperativity might achieve the observed result. For the simulations shown in Fig.…”
Section: A Virtual Cell To Explain Dynamic Ca 21 Redistributions Durimentioning
confidence: 90%
“…7, B and C). The rationale for this was that most EF-hand Ca 21 binding proteins have four Ca 21 binding sites, and cooperativity has been observed in several cases (Iida, 1988;Leathers et al, 1990;Morimoto and Ohtsuki, 1994;Olwin and Storm, 1985;Teleman et al, 1983). However, we stress that these changes were introduced so that our simulations better reproduced the measured fluorescence changes in the cytosol and not because we have any experimental evidence that the endogenous Ca 21 binding protein in adrenal chromaffin cells has four Ca 21 binding sites or exhibits positive cooperativity.…”
Section: Ca 21 Clearance and Decay Of Ca 21 Signalsmentioning
confidence: 95%
“…The molecular mechanisms of this SLdependent effect are currently debated but thought to result, at least in part, from changes in lattice spacing between the thin and thick filaments, and/or changes in myosin crossbridge orientation that increase the probability of myosin binding to actin at longer SLs (9,11,17,20,25,41,42). Furthermore, crossbridge binding enhances Ca 2ϩ binding to troponin (cTn) in cardiac muscle, a unique form of cooperative thin filament activation whose mechanism is currently not well understood (10,11,19,32). The net result of these interactions is an apparent increase in Ca 2ϩ sensitivity of thin filament activation at longer SLs, whereby a given submaximal Ca 2ϩ concentration ([Ca 2ϩ ]) results in greater contractile force development.…”
mentioning
confidence: 98%
“…On Ca 2ϩ binding to TnC, a Ca 2ϩ -induced interaction of TnC with TnI relieves the inhibitory action of TnI exerted on the thin filament and enables the myosin head to cyclically interact with actin in the thin filament and generate force. The Ca 2ϩ sensitivity of muscle contraction is determined by the Ca 2ϩ -binding affinity of TnC, which is dynamically altered through interaction with TnI and TnT in the myofilament lattice (3)(4)(5)(6)(7)(8).…”
mentioning
confidence: 99%